2021
DOI: 10.1002/lipd.12298
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of High‐Oleic Soybean Oil Improves Lipid and Lipoprotein Profile in Humans Compared to a Palm Oil Blend: A Randomized Controlled Trial

Abstract: Partially hydrogenated oils (PHO) have been removed from the food supply due to adverse effects on risk for coronary heart disease (CHD). High-oleic soybean oils (HOSBO) are alternatives that provide functionality for different food applications. The objective of this study was to determine how consumption of diets containing HOSBO compared to other alternative oils, with similar functional properties, modifies LDL cholesterol (LDLc) and other risk factors and biomarkers of CHD. A tripleblind, crossover, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Recently, high oleic soybean shows significant geographical expansion over several regions in the United States (Napolitano et al, 2018). The oils from high oleic soybean contains a large proportion of oleic acid (60%–90%) which yield stronger oxidative stability than regular plant oils, and have been used as a replacement for partially hydrogenated oil (Baer et al, 2021; Napolitano et al, 2018). Besides the good resistance to oxidation, consumption of diet containing high oleic acid soybean oil tends to reduce total cholesterol and low‐density lipoprotein cholesterol, thus, providing beneficial health effects (Huth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high oleic soybean shows significant geographical expansion over several regions in the United States (Napolitano et al, 2018). The oils from high oleic soybean contains a large proportion of oleic acid (60%–90%) which yield stronger oxidative stability than regular plant oils, and have been used as a replacement for partially hydrogenated oil (Baer et al, 2021; Napolitano et al, 2018). Besides the good resistance to oxidation, consumption of diet containing high oleic acid soybean oil tends to reduce total cholesterol and low‐density lipoprotein cholesterol, thus, providing beneficial health effects (Huth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional soybean oil contains higher levels of linoleic acid, which has a greater tendency to oxidize and reduce the shelf-life for cooking oils. HOSBO contains reduced levels of linoleic acids and significantly higher levels of oleic acids, which are not only more shelf-stable but also have been found to reduce the risks of coronary heart disease relative to consuming other edible oils ( Lichtenstein et al., 2006 ; Fehr, 2007 ; Baer et al., 2021 ). These characteristics carry value for consumers and food processors, who are likely to pay a premium for farmers to produce HOSBO for food uses.…”
Section: Evidence From High Oleic Soybean Varietiesmentioning
confidence: 99%
“…In 2018, the US FDA determined that there is credible, although not conclusive, evidence to support a qualified health claim that edible oils containing at least 70% oleic acid per serving may reduce the risk of CHD. More recently, in a triple-blind randomized human trial (n = 60), it was revealed that diets containing HO soybean oils could promote lipid and lipoprotein profiles that are associated with reduced cardiovascular disease risk compared to diets containing palm oil, which is rich in palmitic acid (Baer et al 2021).…”
Section: Modification Of the Seed Oil Profile Via Silencing/editing O...mentioning
confidence: 99%